Rancang Bangun Sistem Pencampur Minuman Jamu Otomatis Berbasis Mikrokontroler - Ratna Aisuwarya; Nurul Fatimah (JITCE (Journal of Information Technology and Computer Engineering), 2019)
People in general have a desire to live a healthy life. One way to keep health is by consuming herbal drinks, one of them is known as jamu. Jamu which is commonly found is "jamu gendong" which is a home-based herbal product that is marketed in the form of liquid in the bottle. When buying jamu, the seller will mix various types of jamu by pouring jamu from each bottle into a glass according to the buyer's request. However, mixing several types of jamu is carried out using the seller estimate, so the dosage of several types of jamu to the glass will vary according to the pouring. The purpose of this research is to make a arduino Mega based automatic jamu beverage mixing system. This system uses an LDR sensor to detect the presence of a glass with a resistance value read by an LDR sensor is > 500 ohm and a DC motor can move by the stirrer. The selection of the jamu menu's is done by pressing the keypad button from the code '1' to the code '8'. After the menu is selected, the jamu will flow to the glass and the volume of jamu will be calculated using a water flow sensor that uses multiplier values. For the volume of 150 mL is used to multiplie factor 3.7 , for the volume of 100 mL is used to multiplie factor 2.9 , and for the volume of 50 mL is used to multiplie factor 1.2.